Emergency Surgical Retrieval of an Amplatzer Septal Occluder Device Embolization - Atmani, Noureddine; Mitchell, Julia; Metton, Olivier; Ninet, Jean (Cardiology and Cardiovascular Medicine, 2017)
Atrial septal defect (ASD) is a common congenital heart defect. Transcatheter closure become now the standard approach for ostium secondum type ASD closure against surgery. However, this procedure is not free of complications Device migration is the most common complication. We report a case of an obstruction of tricuspid valve by migration of a transcatheter ASD device occlude in a 9 years-old girl reveled by severe ventricular arrhythmias. She underwent successful emergent surgical removal under cardiopulmonary bypass and ASD closure with a synthetic patch. The postoperative course was favorable.